Check-list of North Korean Orthoptera Based on the Specimens Deposited in the Hungarian Natural History Museum - Kim, Tae-Woo; Puskás, Gellért (Zootaxa, 2012)
Beginning with Hungarian expeditions to Korean peninsula in 1970, many Korean biological specimens have accumulat-ed in the collections of the Hungarian Natural History Museum. The collections have informative value to understand EastAsian biota. Here, North Korean Orthopterans are examined and checked; 73 species are listed and collecting data formore than 1,441 individuals is provided. A joint research project was accomplished in the year 2010 between the Hungar-ian Natural History Museum and the National Institute of Biological Resources. The project produced a total of 123 spec-imens of 26 North Korean Caeliferan species which are newly placed in the Entomological Collection of the NationalInstitute of Biological Resources. A transpalaearctic long-horned grasshopper Bicolorana bicolor (Philippi, 1830) is reported for the first time from North Korean fauna.